Inverse reliefs in virtual globes (Ágora de Heterodoxias, 2015)
Most users of Virtual Globes (Google Maps, Microsoft Bing, Apple Maps etc.) interpret images with an inverse relief (they see ridges that are actually valleys and rivers that are actually mountain ranges) being unaware of it. This happens in 80% of Virtual Globe users who observe land in the Northern Hemisphere. The phenomenon does not occur in the Southern Hemisphere because the land is illuminated by the Sun from the north. The fact that most of the Earth's Northern Hemisphere is illuminated by the Sun from the south makes southern slopes be illuminated and northern slopes be in shadow. This paper aims at showing evidence of this problem, explaining visual perceptual limitations, showing that the effect occurs because the Northern Hemisphere is illuminated from the south and providing some solution that could be easily implemented by those responsible for geoportals that use these Virtual Globes or use their own orthoimagery as georeferencing basis for their geoportals. The wide use made of land pictures offered by Virtual Globes, mainly by Google Maps, and their inclusion in a great number of applications that use land images as a basis to show other land features, require that the land relief perceived by the user should be perceptually adequate. Moreover, these Virtual Globes providing mostly an inverse relief are used in many institutional geoportals (Cadasther, displays of Spatial Data Infrastructures) as the basis for referencing other land features and, therefore, a correct display of the relief is essential
Keywords: false relief; virtual globes; relief inversion; map visualization software